I posti dei rifiuti. Badara Ngom e la discarica di Mbeubeuss - Luca Rimoldi (Archivio Antropologico Mediterraneo)
This article describes some aspects of the social life of waste, contributing to the debate on anthropology of waste, and focusing on the living and working spaces of the Mbeubeuss landfill, on the outskirts of Dakar. From a theoretical point of view, waste escapes a rigid categorization, yet they create relationships, spaces and landscapes delimited and defined by the policies and (formal and informal) practices of their own management. The reflection presented here, based on ethnographic data collected between 2016 and 2019 with a group of formal and informal workers of Mbeubeuss, aims to analyze the construction of social and relational spaces in the Dakar landfill. I intend to demonstrate how value is not only a representation of social relations, but how it contributes to orienting life trajectories, and to maintaining a social order.